2016
DOI: 10.1111/jeb.12790
|View full text |Cite
|
Sign up to set email alerts
|

Paternal‐specific S‐allele transmission in sweet cherry (Prunus avium L.): the potential for sexual selection

Abstract: Homomorphic self-incompatibility is a well-studied example of a physiological process that is thought to increase population diversity and reduce the expression of inbreeding depression. Whereas theoretical models predict the presence of a large number of S-haplotypes with equal frequencies at equilibrium, unequal allele frequencies have been repeatedly reported and attributed to sampling effects, population structure, demographic perturbation, sheltered deleterious mutations or selection pressure on linked ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Thus, Arunkumar et al (2013) showed in Capsella grandiflora that selection had more detectable effects on pollen-exclusive genes than on seedling-exclusive genes whereas Chettoor et al (2014) observed that selective pressures based on the male gametophytic function result in high effects on the maize plant genome. Additional work assessing paternity of the offspring shows that pollen tube competition could also result in sexual selection in plants ( Hedhly et al, 2015 ).…”
Section: Toward a Major Control Of The Sporophytementioning
confidence: 99%
“…Thus, Arunkumar et al (2013) showed in Capsella grandiflora that selection had more detectable effects on pollen-exclusive genes than on seedling-exclusive genes whereas Chettoor et al (2014) observed that selective pressures based on the male gametophytic function result in high effects on the maize plant genome. Additional work assessing paternity of the offspring shows that pollen tube competition could also result in sexual selection in plants ( Hedhly et al, 2015 ).…”
Section: Toward a Major Control Of The Sporophytementioning
confidence: 99%